The effects of polyester microfibres on the development and seed yield of white mustard (Sinapis alba L.) - Harrison, Eleanor Grace; Reiling, Kevin; Halfpenny, Richard Kenneth; Gwinnett, Claire (Frontiers in Environmental Science, 2024)
Microplastics are found in agricultural soils worldwide; however, little is known about the impacts of this ubiquitous pollutant on the growth and development of crops. Microfibres are one of the dominant microplastic types found in agricultural soils. Sources of microfibres in the agricultural environment are multiple, including soil amendment applications, wastewater irrigation and atmospheric deposition, with agricultural soils subsequently acting as an accumulating sink for plastics. A key consideration in an agricultural setting is yield; the seed yield is critical, as this is the part with economic value. In this study, the effects of polyester microfibres (a common plastic type found in agricultural soils) were tested on Sinapis alba (white mustard) to assess any changes to the development and reduction in seed yield of the plant. Specifically, this study assessed flower production, seed yield (mass), pod-to-seed ratio, and chlorophyll fluorescence. Polyester microfibres were demonstrated to act as a stressor to S. alba, changing the chlorophyll fluorescence values, reducing the flower number, and in turn, reducing the pod-to-seed ratio. This study provides evidence that microfibres could reduce seed yield but that further research is required to elucidate the mechanisms by which these changes are occurring.